2018
DOI: 10.1001/jamanetworkopen.2018.1580
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Complications ofCoxiella burnetiiInfections From the French National Reference Center for Q Fever

Abstract: Key Points Question What are the characteristics and clinical presentations of Coxiella burnetii infection using 21st-century–clarified definitions? Finding In a cohort study of 2434 patients with Q fever, the following new critical Q fever foci were identified: acute endocarditis, lymphadenitis, and bone marrow involvement in hemophagocytic syndrome. Lymphadenitis is a risk factor for lymphoma, and the elevation of IgG anticardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
107
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(125 citation statements)
references
References 63 publications
(54 reference statements)
2
107
2
1
Order By: Relevance
“…Even though persons with underlying immunosuppression are at increased risk for developing Q fever, there are few reported cases of Q fever in SOT recipients. In a recent cohort study evaluating over 2000 patients with Q fever from the French National Reference Center for Q fever from 1991 to 2016, only 14 patients had SOTs, most of which were renal transplants . Two‐thirds of patients who were classified as immunosuppressed experienced acute Q fever, though details of these patients are lacking.…”
Section: Discussionmentioning
confidence: 67%
“…Even though persons with underlying immunosuppression are at increased risk for developing Q fever, there are few reported cases of Q fever in SOT recipients. In a recent cohort study evaluating over 2000 patients with Q fever from the French National Reference Center for Q fever from 1991 to 2016, only 14 patients had SOTs, most of which were renal transplants . Two‐thirds of patients who were classified as immunosuppressed experienced acute Q fever, though details of these patients are lacking.…”
Section: Discussionmentioning
confidence: 67%
“…SOT recipients comprised of only 14 (0.6%) patients (10 renal, 3 liver, and 1 heart transplant) among a large cohort of 2434 patients with Q fever over a 26‐year period from the French National Reference Center for Q fever. However, detailed information of these cases is not provided . Four other cases of Q fever in SOT recipients were recently reviewed by Petty et al One other reported case involved a simultaneous heart and kidney transplant recipient, where the diagnosis of Q fever endocarditis was missed before transplant leading to mitral and aortic valve regurgitation in the transplanted heart .…”
Section: Discussionmentioning
confidence: 95%
“…Our patient had chronic Q fever pneumonitis (or “persistent focal pneumonitis” as some experts prefer to call it) based on elevated phase I IgG (≥800). Unlike acute Q fever which is characterized by elevated phase II IgM and IgG and low or nonexistent phase I IgG, in chronic infection, there is a phase switch with phase I IgG titer being typically ≥800 (although in some chronic infections like lymphadenitis and chronic interstitial lung disease, the cutoff for phase I IgG can be lower, eg, ≥400) …”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations